DETERMINATION OF THE DYNAMIC PARAMETERS OF THE MOBILE FIRE STATION OPERATOR IN THE FREQUENCY DOMAIN - Abramov, Y.; Sobyna, V. (Municipal economy of cities. Series: «Economy science», 2023)
Determination of the dynamic parameters of the operator of the mobile fire apparatus is based on the use of its amplitude-frequency and phase-frequency characteristics, the value of which is used at a priori set frequency. The value of these frequency characteristics of the operator of the mobile fire apparatus is used as initial data. Using the exponent and trigonometric form of the expression for the complex transfer function of the operator of the mobile fire apparatus, the functional dependence between its phase-frequency characteristic and dynamic parameters - the delay time and the operator's time constant - was obtained. This functional dependence is given in the form of two additive components, one of which is represented by a trigonometric function, the argument of which is the value of the phase-frequency characteristic of the operator and its delay time. The second additive component is a function of the time constant of the operator. The constructed functional dependence is used to determine the delay time of the operator of the mobile fire apparatus, provided that another dynamic parameter - the time constant - is determined using the amplitude-frequency characteristic of the operator and the normative value of its transmission coefficient. A graphical interpretation is given for the constructed functional dependence, which can be used as a component of the algorithm when determining the dynamic parameters of the operator of a mobile fire extinguisher.The algorithm for determining the dynamic parameters of the operator of a mobile fire installation is presented, which is presented in verbal form. The developed algorithm for determining the dynamic parameters of the operator of the mobile fire apparatus during its implementation involves the use of a graphical interpretation of the functional dependence between the delay time and the time constant of the operator of the mobile fire apparatus.The presented algorithm differs from the known ones by the simplicity of its implementation, which is ensured by reducing the number of a priori frequencies used to determine the values of the frequency characteristics by four times. An example of the implementation of the algorithm for determining the dynamic parameters of the operator of a mobile fire installation is given.